Leveraging Autofluorescence for Tumor Detection, Diagnosis, and Accurate Excision with Surgical Margin Assessment in Tumor Excision - Antonis Perdiou; Ramona Dumitrescu; Daniela Jumanca; Octavia Balean; Ruxandra Sava-Rosianu; Serban Talpos; Dacian Virgil Lalescu; Atena Galuscan (Dentistry Journal)
Background/Objectives: Oral cancer ranks among the top ten cancers globally, with a five-year survival rate below 50%. This study aimed to evaluate the effectiveness of autofluorescence-guided surgery compared to standard surgical methods in identifying tumor-free margins and ensuring complete excision. Methods: A prospective cohort of 80 patients was randomized into two groups: the control group underwent excision with a 10 mm margin based on clinical judgment, while the experimental group used autofluorescence guidance with a 5 mm margin beyond fluorescence visualization loss. Autofluorescence imaging was performed using the OralID device, which employs a 405 nm excitation laser to detect abnormal tissue. Ethical approval was obtained from the “Spitalul Clinic Municipal de Urgență Timișoara” Ethics Committee (approval number 08/26.02.2021), and the trial was registered at the University of Medicine and Pharmacy Timisoara (trial no. 59/25.11.2021). A double analysis was conducted: a primary analysis of the full cohort and a subgroup analysis focusing on squamous cell carcinoma (control: n = 19; experimental: n = 24). Histopathological analysis was the gold standard for margin evaluation, with margins coded as tumor-free margins (0), close (1), or infiltrated (2). Results: Statistically significant differences were observed in tumor-free margins between the control (73.17%) and experimental (97%) groups (p = 0.003). Subgroup analysis for SCC showed no significant difference (control: 84.21%; experimental: 95.83%; p = 0.306). Tumor location also differed significantly (p = 0.011), while other baseline variables, such as tumor type and patient characteristics, showed no significant differences. Conclusions: Autofluorescence-guided surgery improves the detection of tumor-free margins and may serve as an effective adjunct in oral cancer management. Larger studies are recommended to confirm these findings.